Long‐term outcome of postmenopausal women with non‐atypical endometrial hyperplasia on endometrial sampling. (28th February 2020) - Rotenberg, O.; Fridman, D.; Doulaveris, G.; Renz, M.; Kaplan, J.; Gebb, J.; Xie, X.; Goldberg, G. L.; Dar, P.
ABSTRACT: Objective: To assess the long‐term outcome of postmenopausal women diagnosed with non‐atypical endometrial hyperplasia (NEH). Methods: This was a retrospective study of women aged 55 or older who underwent endometrial sampling in our academic medical center between 1997 and 2008. Women who had a current or recent (< 2 years) histological diagnosis of NEH were included in the study group and were compared with those diagnosed with atrophic endometrium (AE). Outcome data were obtained until February 2018. The main outcomes were risk of progression to endometrial carcinoma and risk of persistence, recurrence or new development of endometrial hyperplasia (EH) ('persistent EH'). Logistic regression analysis was used to identify covariates that were independent risk factors for progression to endometrial cancer or persistent EH. Results: During the study period, 1808 women aged 55 or older underwent endometrial sampling. The median surveillance time was 10.0 years. Seventy‐two women were found to have a current or recent diagnosis of NEH and were compared with 722 women with AE. When compared to women with AE, women with NEH had significantly higher body mass index (33.9 kg/m 2 vs 30.6 kg/m 2 ; P = 0.01), greater endometrial thickness (10.00 mm vs 6.00 mm; P = 0.01) and higher rates of progression to type‐1 endometrial cancer (8.3% vs 0.8%; P = 0.0003) and persistent NEH (22.2% vs 0.7%; P < 0.0001). They also had a higher rate of progression to any type of uterine cancer or persistent EH (33.3% vs 3.5%; P < 0.0001). Women with NEH had a significantly higher rate of future surgical intervention (51.4% vs 15.8%; P < 0.0001), including future hysterectomy (34.7% vs 9.8%; P < 0.0001). On multivariable logistic regression analysis, only NEH remained a significant risk factor for progression to endometrial cancer or persistence of EH. Conclusions: Postmenopausal women with NEH are at significant risk for persistent EH and progression to endometrial cancer, at rates higher than those reported previously. Guidelines for the appropriate management of postmenopausal women with NEH are needed in order to decrease the rate of persistent disease or progression to cancer. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.